2010
DOI: 10.1111/j.1365-2125.2010.03615.x
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics and Bayesian estimator of mycophenolic acid in children with idiopathic nephrotic syndrome

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• MMF has been proposed as a treatment of steroid-dependent nephrotic syndrome and in the recent years, several studies have suggested its positive effect in preventing relapses. WHAT THIS PAPER ADDS• The population pharmacokinetics of MPA was first evaluated in children with idiopathic nephrotic syndrome and data fitted well with a two-compartment model with first-order absorption and lag time.• Body weight and serum albumin had a significant impact on oral clearance. •… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
93
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(99 citation statements)
references
References 45 publications
5
93
0
1
Order By: Relevance
“…Median as well as mean dose-normalized MPA AUC 12 (44.7 lg h/mL ± 24.9 lg h/mL) obtained in our study were comparable to the literature data concerning children with nephrotic syndrome (Zhao et al, 2010;Baudouin et al, 2012), in stable period after renal transplantation (Weber et al, 2008) or in liver transplant recipients (Barau et al, 2011;Lobritto et al, 2007). In our study, dose-normalized MPA AUC 12 was lower in children with proteinuria, however, it was not statistically significant and proteinuria was observed also in the child with one of the highest MPA AUC 12 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Median as well as mean dose-normalized MPA AUC 12 (44.7 lg h/mL ± 24.9 lg h/mL) obtained in our study were comparable to the literature data concerning children with nephrotic syndrome (Zhao et al, 2010;Baudouin et al, 2012), in stable period after renal transplantation (Weber et al, 2008) or in liver transplant recipients (Barau et al, 2011;Lobritto et al, 2007). In our study, dose-normalized MPA AUC 12 was lower in children with proteinuria, however, it was not statistically significant and proteinuria was observed also in the child with one of the highest MPA AUC 12 .…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, the variability of MMF metabolites pharmacokinetics in children may be affected by various factors (treatment duration, therapeutic indication, drugs co-administered, genetic, physiological and environmental factors as well as kidney or liver dysfunction) (Filler, 2007(Filler, , 2006Parant et al, 2009;Brown et al, 2002;Jacobson et al, 2008;Ghio et al, 2009). There is little data in the literature on the pharmacokinetics of MMF metabolites in children (Filler, 2007(Filler, , 2006, especially diagnosed with nephrotic syndrome (Zhao et al, 2010;Saint-Marcoux et al, 2011). Additionally, food intake may be one of the factors influencing MMF pharmacokinetics.…”
Section: Introductionmentioning
confidence: 94%
“…Dorresteijn et al, in children with SDNS, also reported low MPA AUC (27 mg*h/L) in one child who had three relapses within 6 months on MMF, whereas six children with AUC between 40 and 99 mg*h/L had no relapses [18]. Additional studies in pediatric patients with [31,32]. The frequency of adverse effects in our patients was similar to those reported in studies using the same MMF dosage.…”
Section: Discussionsupporting
confidence: 91%
“…From a practical point of view, we stated a priori that the best MAP Bayesian estimator should be selected within 3-4 h post dose (in order to limit outpatients' stay) and the number of samplings should not exceed three [17,18].The selection of the different time points was based on their respective prediction performance.…”
Section: Maximum a Posteriori Probability Bayesian Estimatormentioning
confidence: 99%
“…Owing to the limited number of patients in this study, the cross-validation method was used to evaluate MAP Bayesian estimator [17]. The full data set was randomly divided into three subsets (each one contains one-third of the pharmacokinetic profiles).…”
Section: Maximum a Posteriori Probability Bayesian Estimatormentioning
confidence: 99%